Enhance Daylighting Quality of Architecture Studio in Faculty of Architecture, Urban Design and Creative Arts, Mahasarakham University - Intarakulchai ฺBorirak (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This paper outlines the results of an empirical investigation for improving an architecture studio in theFaculty of Architecture, Urban Design and Creative Arts, Mahasarakham University. The main objective of thisresearch is to increase an appropriate amount of natural-light for the mentioned room, mindful of recommendationsof Illuminating Engineering Association of Thailand (TIEA), as well as to reduce electric energy consumptionof artificial lighting throughout the day. Notably, the construction drawings of this room have been analyzed inorder to identify the characteristics and to determine developing guidelines for the most suitable improvingconditions, bearing in mild the main building structure should not be affected – 3D model of the roomrepresented in DIALux lighting simulation software. The result shows that the modification of four maincomponents together including ceiling, interior partitions, voids and adding horizontal light pipe system maywell stimulate possible improvements. The recommended average annual illuminance referred to TIEA is lowerthan 750 LUX. This modification could increase illuminance up to 70.02% and the light-quality is better thanการปรับปรุงคุณภาพแสงธรรมชาติของห้องปฏิบัติการสถาปัตยกรรมในคณะสถาปัตยกรรมศาสตร์ ผังเมือง และนฤมิตศิลป์ มหาวิทยาลัยมหาสารคามEnhance Daylighting Quality of Architecture Studio in Faculty of Architecture,Urban Design and Creative Arts, Mahasarakham Universityบริรักษ์ อินทรกุลไชยBorirak Intarakulchaiคณะสถาปัตยกรรมศาสตร์ ผังเมือง และนฤมิตศิลป์ มหาวิทยาลัยมหาสารคาม จังหวัดมหาสารคาม 44150Faculty of Architecture, Urban Design and Creative Arts, Mahasarakham University, Maha Sarakham, 44150, ThailandE-mail: boririntara@hotmail.com46 JARS 10(2). 2013other guidelines. In the light of finding, the knowledge of this research can be applied to use for reduceelectric energy consumption for artificial lighting during daytime, and can be used as a reference for buildingdevelopment supporting “Going Green” policy of Mahasarakham University.